In Vitro Photodynamic Treatment Modality for A375 Melanoma Cell Line Using a Sulphonated Aluminum Phthalocyanine Chloride-Photosensitizer-Gold Nanoparticle Conjugate - Bridgette Mkhobongo; Rahul Chandran; Heidi Abrahamse (MDPI AG, 2022)
Metastatic melanoma cancer stem cells are subpopulations that have been identified and linked to tumor progression, immunoevasive behavior, drug resistance, and metastasis, leading to a poor prognosis. Photodynamic therapy (PDT) is an approach to eradicate cancer through a photochemical process which directly generates reactive oxygen species (ROS). This study investigated the impact of PDT using an aluminum phthalocyanine gold nanoparticle (AlPcS4Cl-AuNP) conjugate for targeting melanoma stem cells. The isolated stem cells were irradiated at 673.2 nm with a radiant exposure of 5 J/cm2. Post-irradiation signs of cell death were determined using microscopy and biochemical assays. A possible enhanced effect of ROS in inducing cell death could be seen when AlPcS4Cl was conjugated to AuNPs. Nanoparticles as carriers promote the efficient cellular uptake of photosensitizers, enhancing organelle accumulation and the targeted therapy of cancerous cells. A biochemical assay revealed significant post-irradiation signs of cell death. The measurement of adenosine triphosphate (ATP) content revealed a decrease in cell proliferation. The study suggested an approach directed at expanding the knowledge on PDT to improve cancer treatment. Understanding the cell death mechanism through which ROS influence cancer stem cells (CSCs) is, therefore, useful for improving PDT efficiency and preventing tumor recurrence and metastasis.